2009
DOI: 10.1097/dad.0b013e31818d3ac7
|View full text |Cite
|
Sign up to set email alerts
|

Symplastic Glomus Tumor: A Case Report

Abstract: Symplastic glomus tumors are defined as glomus tumors with a high-grade nuclear pleomorphism in the absence of any other malignant features, such as large size, deep location, infiltrative growth, mitotic activity, or necrosis. Only 11 cases have been reported so far in the English literature. It could be a challenge for pathologists who have no experience with it because the tumor can show marked nuclear atypia and pleomorphism. Despite its high nuclear grade, a symplastic glomus tumor itself has a benign bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 1 publication
1
8
0
Order By: Relevance
“…Clinical and pathological assessment of 52 previously diagnosed atypical or malignant glomus tumors showed that high nuclear grade alone was not associated with an increased metastatic risk 1 . This type of glomus tumor is classified as a symplastic glomus tumor and 14 cases have been reported to date 1–6 . A comparison with cases of classical and symplastic glomus tumors reported previously showed that our case shared several factors with the typical clinical picture, including age of onset, female predominance, size and depth of the tumor, and digital distribution.…”
supporting
confidence: 49%
“…Clinical and pathological assessment of 52 previously diagnosed atypical or malignant glomus tumors showed that high nuclear grade alone was not associated with an increased metastatic risk 1 . This type of glomus tumor is classified as a symplastic glomus tumor and 14 cases have been reported to date 1–6 . A comparison with cases of classical and symplastic glomus tumors reported previously showed that our case shared several factors with the typical clinical picture, including age of onset, female predominance, size and depth of the tumor, and digital distribution.…”
supporting
confidence: 49%
“…One of the hypotheses to explain pain intensity is based on tumor expansion, that is, as it is contained in a pseudocapsule, its growth is restricted, which leads to the necrosis of the central cells and their replacement by connective tissue. Another hypothesis to justify pain is tumor site, as it arises in the myoneural junction (11,13,14).…”
Section: Operative Technique and Resultsmentioning
confidence: 99%
“…One of the hypotheses to explain pain intensity is based on tumor expansion, that is, as it is contained in a pseudocapsule, its growth is restricted, which leads to the necrosis of the central cells and their replacement by connective tissue. Another hypothesis to justify pain is tumor site, as it arises in the myoneural junction 13,15,16 . The region most frequently affected by an extremity glomangioma is the dermis, the subcutaneous cell tissue, particularly in the nail bed 17 , because there is little resistance to its development there, and not in small-caliber arteries, as Kamarashev et al 1 used to believe.…”
Section: Discussionmentioning
confidence: 99%